MAKNA TUTURAN LI PED’JO DALAM TARIAN PEDO’A PADA UPACARA ADAT PANEN MASYARAKAT SABU DI DESA RAEMUDE KECAMATAN SABU BARAT KABUPATEN SABU RAIJUA - Nursia Tuka Lay; Labu Djuli; Margareta P. E. Djokaho (STKIP Subang, 2026)
This study aims to describe the form of presentation and uncover the meaning of Li Ped'jo’s recitations in the Pedo'a dance during the traditional harvest ceremony of the Sabu community in Raemude Village, West Sabu Subdistrict, Sabu Raijua Regency. This study employs a qualitative approach using descriptive methods. The research data consists of the Li Ped'jo narrative recited by Mone Ped'jo during the performance of the Pedo'a dance. The data was collected through observation, interviews, documentation, and note-taking, and was then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The research findings show that the performance of the Pedo'a dance consists of Mone Ped'jo as the leader of the chant, Da'u Pedo'a as the dancers, the wearing of traditional attire, kedu'e as the rhythmic accompaniment, dance movements, and Li Ped'jo’s recitation as a medium for conveying cultural messages. Li Ped’jo’s recitation contains four main meanings: a religious meaning as an expression of gratitude and supplication to God; a sociological meaning that reflects togetherness and solidarity; a historical meaning that describes the origins of the Sabu people; and an aesthetic meaning evident through the beauty of the language, rhythm, and word choice. Thus, Li Ped'jo serves not only as a dance accompaniment but also as a medium for passing down cultural, moral, and spiritual values to the Sabu community.